Mass supervision in the South: 10 years of the reform to alternative sanctions in Chile - Morales, Ana María (Punishment, probation and parole, 2024)
In this chapter, I analyse the implementation of the reform to the regimen of alternatives to prison in Chile which occurred in 2013 and how the reform affected how punishment is conceived and translated into practice by professionals supervising probation and community services. The findings suggest the reform that led to the new ‘substitutive sanctions’ also introduced a new risk-oriented-managerial culture that has permeated how punishment is currently enforced and envisaged by supervision professionals; a situation that has been deepening over the years, not only through practice, but also via on-going training that has helped to generate the emergence of ‘cultural’ capital that distinguishes supervision professionals from the larger organisation. This has been combined with a rapid expansion in the use of substitutive sanctions, especially probation and ‘partial reclusion’ that can aptly be analysed under the ‘mass supervision’ premise.